Genome of Methylomonas sp. AM2-LC, representing a methanotrophic bacterial species isolated from water column of a boreal, oxygen-stratified lake - Rissanen, Antti J.; Mangayil, Rahul; Khanongnuch, Ramita (Frontiers Media S.A., 2024)
Methanotrophic bacteria are a special group of bacteria that consume methane as their energy and carbon source. They are roughly divided into aerobic gammaproteobacterial, alphaproteobacterial and verrucomicrobial methanotrophs (that use O2 as their primary electron acceptor), and anaerobic bacteria of genus Candidatus Methylomirabilis (that use nitrite to oxidize methane) (Guerrero-Cruz et al., 2021). Methanotrophic bacteria play a crucial role in reducing the methane emissions from natural methanogenic ecosystems, like rivers, lakes and wetlands (Hanson and Hanson, 1996). They are also actively harnessed for their biotechnological potential to mitigate methane emissions from anthropogenic ecosystems (e.g., biofilters at landfills) and to convert methane in biogas and natural gas into various value-added products (e.g., single-cell protein and bioplastics) (Strong et al., 2015). Comparative genomics of bacteria form the basis of the current bacterial taxonomy, like that of methanotrophic bacteria (Orata et al., 2018). In addition to comparative analysis, genome sequences of methanotroph isolates provide an important backbone database for taxonomic and functional analysis of the vast and constantly increasing shotgun metagenomic data, especially metagenome-assembled genomes (MAG) of putative methanotrophs, collected from environment (Buck et al., 2021; Khanongnuch et al., 2023). Furthermore, genomic data provide crucial insights into potentially novel and testable metabolisms in methanotrophic bacteria, relevant both to the understanding of environmental methane cycling and for biotechnological applications, such as fermentation, i.e., conversion of methane to organic acids and H2 (Kalyuzhnaya et al., 2013), denitrification (Kits et al., 2015), extracellular electron transfer (Zheng et al., 2020), and oxidation of alternative electron donors (Gwak et al., 2022). Genetic engineering of methanotrophs to enhance their methane consumption and bioconversion efficiencies, and to increase the range of methane-derived products, also benefit greatly from the genomic data (Henard and Guarnieri, 2018; Jeong et al., 2023). Here, we report the genome sequence of a strain Methylomonas sp. AM2-LC, which was isolated from the water column of a boreal, humic, O2-stratified lake, located in Southern Finland. It represents a putatively novel species of Methylomonas sp., a methanotroph genus widely present in various methanogenic ecosystems (Bussmann et al., 2021; Danilova et al., 2013; Hoefman et al., 2014; Ogiso et al., 2012; Zhu et al., 2020), and an attractive methane bioconversion candidate (Patel et al., 2018; Patel et al., 2022; Tikhonova et al., 2023).
Keywords: methanotroph; greenhouse gases; methane bioconversion; Methylomonas; natural gas; lakes; biogas; climate change